2013
DOI: 10.1111/dote.12131
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between complaints of night-time heartburn and sleep-related gastroesophageal reflux

Abstract: This study investigated whether the complaint of night-time heartburn (NHB) as opposed to daytime heartburn (DHB) is a reliable reflection of actual sleep-related reflux events. Three groups of individuals were studied: individuals with complaints of NHB at least twice per week (n = 24), individuals with complaints of DHB (n = 23), and normal participants without any complaints of regular heartburn during the day or night (n = 25). All three groups were studied on one occasion with combined pH monitoring and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the nighttime heartburn group had significantly more sleep‐related reflux events (total acid contact time and average duration of reflux events) compared with both the daytime heartburn group and the control group. Therefore, the nighttime heartburn group had significantly worse parameters with regard to objective and subjective sleep quality . Risk factors for GERD‐related sleep disturbances include smoking, alcohol use, and higher grades of esophagitis; these are among the more severe typical reflux symptoms during the daytime .…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the nighttime heartburn group had significantly more sleep‐related reflux events (total acid contact time and average duration of reflux events) compared with both the daytime heartburn group and the control group. Therefore, the nighttime heartburn group had significantly worse parameters with regard to objective and subjective sleep quality . Risk factors for GERD‐related sleep disturbances include smoking, alcohol use, and higher grades of esophagitis; these are among the more severe typical reflux symptoms during the daytime .…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
“…Therefore, the nighttime heartburn group had significantly worse parameters with regard to objective and subjective sleep quality. 51 Risk factors for GERD-related sleep disturbances include smoking, alcohol use, and higher grades of esophagitis; these are among the more severe typical reflux symptoms during the daytime. 50 A previous study compared the prevalence of nGER symptoms in OSA patients and in the general population and indicated that the prevalence of frequent nGER symptoms was increased in the OSA patients (10.2% vs. 5.5%; P < 0.001).…”
Section: Association Of Nocturnal Symptoms and Sleep Disordermentioning
confidence: 99%